Relevance of Target-Organ Lesions as Predictors of Mortality in Patients with Diabetes Mellitus - Bianco,Henrique Tria (2014)
Background: Patients with diabetes are in extract higher risk for fatal cardiovascular events. Objective: To evaluate major predictors of mortality in subjects with type 2 diabetes. Methods: A cohort of 323 individuals with type 2 diabetes from several regions of Brazil was followed for a long period. Baseline electrocardiograms, clinical and laboratory data obtained were used to determine hazard ratios (HR) and confidence interval (CI) related to cardiovascular and total mortality. Results: After 9.2 years of follow-up (median), 33 subjects died (17 from cardiovascular causes). Cardiovascular mortality was associated with male gender; smoking; prior myocardial infarction; long QTc interval; left ventricular hypertrophy; and eGFR <60 mL/min. These factors, in addition to obesity, were predictors of total mortality. Cardiovascular mortality was adjusted for age and gender, but remained associated with: smoking (HR = 3.8; 95% CI 1.3-11.8; p = 0.019); prior myocardial infarction (HR = 8.5; 95% CI 1.8-39.9; p = 0.007); eGFR < 60 mL/min (HR = 9.5; 95% CI 2.7-33.7; p = 0.001); long QTc interval (HR = 5.1; 95% CI 1.7-15.2; p = 0.004); and left ventricular hypertrophy (HR = 3.5; 95% CI 1.3-9.7; p = 0.002). Total mortality was associated with obesity (HR = 2.3; 95% CI 1.1-5.1; p = 0.030); smoking (HR = 2.5; 95% CI 1.0-6.1; p = 0.046); prior myocardial infarction (HR = 3.1; 95% CI 1.4-6.1; p = 0.005), and long QTc interval (HR = 3.1; 95% CI 1.4-6.1; p = 0.017). Conclusions: Biomarkers of simple measurement, particularly those related to target-organ lesions, were predictors of mortality in subjects with type 2 diabetes.